Popularitas Merek di Sosial Media: Analisis Pengaruh Waktu, Konten, dan Interaksi Merek - Tri Hanifawati; Utan Sahiro Ritonga; Euis Evi Puspitasari (Faculty of Economic and Business, 2019)
Social media is an effective media to increase brand popularity. Previous studies found that the brand has significant effects on the consumers purchasing decision. Indicator of brand popularity on social media includes the number of followers, likes, shares, comments, and views of the video. The objective of this study is to analyze the effects of post time, post content, and brand interaction on brand post popularity of Facebook fan page. Data collected through observation of six (6) international top brands on the Facebook fan page. Data were analyzed using logit regression method. The results show that post time, post content, and brand interaction have significant effects on brand popularity. The managerial implication, it is crucial to highlight that Facebook is a useful platform on brand popularity building. Our discussion section shows some suggested in managing the brand based on our results.